Prácticas sostenibles en infraestructura vial (2017)
"The development of road infrastructure projects strongly impacts environment, so it is necessary to include the concept of sustainability in their design and construction. The present graduation project aims at describing the most common sustainable practices used in the area of pavement engineering in the world and to encourage their use. To achieve this goal, a literature review was conducted with the purpose of identifying and describing technologies like the use of recycled materials in the pavement structure or production alternatives that consume less energy. Next, some qualification systems, certifications and methodologies, such as the Life Cycle Analysis (LCA) of a material or project, were described. The latter fulfill the function of evaluating and quantifying the environmental impact generated by the construction, maintenance and operation of road projects." -- Tomado del Formato de Documento de Grado.